2015
DOI: 10.1111/1756-185x.12637
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on 158 Thai patients with juvenile idiopathic arthritis followed in a single center over a 15‐year period

Abstract: Aim: To determine the outcomes of juvenile idiopathic arthritis (JIA) in Thai children.Methods: A retrospective cohort study. All JIA patients in a rheumatology clinic, Ramathibodi Hospital, between July 1997 and December 2012 were enrolled. The patient data were reviewed from medical records. At the most recent follow-up visit, patient outcomes were assessed in three aspects: disease status, functional outcomes and structural damage.Results: Of 168 patients, 158 (94.0%) were assessed in disease status and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 19 publications
2
7
1
Order By: Relevance
“…The second objective is to show cases of JIA and their characteristics in our region, and finally to evaluate the perception of parents and patients with JIA about the care received. The predominance of the polyarticular RF (-) form stands out in our cases, reported, to our knowledge, only in a cohort of Germany 13 , which contrasts with what has been published in other western countries, including national data, where the oligoarticular form predominates 3,4,5,[14][15][16] , and in Asian countries where systemic and enthesitis-related forms predominate 16,17 . The reasons for the predominance of the polyarticular form RF (-) are not clear, and although there was German colonization in this region, there is no history of patients with German ancestors in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…The second objective is to show cases of JIA and their characteristics in our region, and finally to evaluate the perception of parents and patients with JIA about the care received. The predominance of the polyarticular RF (-) form stands out in our cases, reported, to our knowledge, only in a cohort of Germany 13 , which contrasts with what has been published in other western countries, including national data, where the oligoarticular form predominates 3,4,5,[14][15][16] , and in Asian countries where systemic and enthesitis-related forms predominate 16,17 . The reasons for the predominance of the polyarticular form RF (-) are not clear, and although there was German colonization in this region, there is no history of patients with German ancestors in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Worse outcomes in JIA are reported in Hispanic, African American and Asian studies [ 33 , [66] , [67] , [68] ], and in countries with low GDP [ 36 ]. Such observations have multifactorial explanations, including higher prevalence of poor prognosis subtypes in these populations [ 68 ], paucity and poor access to specialist care [ 5 , 36 , 37 , 69 ] with delay to diagnosis and inequity being widely reported [ 5 , 33 , 37 , [69] , [70] , [71] ]. There have been considerable advances in JIA, including biological therapies, and the condition is now regarded as treatable although many treatments are not always affordable or accessible [ 3 , 59 ].…”
Section: Impact Described Through Selected Msk Conditionsmentioning
confidence: 99%
“…The prevalence and incidence rates for JIA were 0.02% and 0.002% per year, respectively. The proportion of sJIA to JIA in Thailand was 33.8% according to a retrospective study from 1997 to 2012, 12 while the proportion of refractory sJIA was around 20.09% based on our data collection from seven tertiary hospitals. Thus, the number of patients with refractory sJIA was 171 cases in 2017, with 17 new cases annually.…”
Section: Methodsmentioning
confidence: 84%
“…11 In Thailand, a retrospective study over a 15-year period from 1997 to 2012 in a single referral centre indicated that sJIA contributes to 33.8% of JIA. 12 …”
Section: Introductionmentioning
confidence: 99%